Meningkatkan Aktivitas Belajar Ipa Melalui Penerapan Metode Stad Pada Siswa Kelas IV - Sunarsih, Sunarsih (Science and Education Journal (SICEDU), 2022)
The purpose of this study was to increase science learning activities through the application of the STAD learning method in Class IV SD Negeri Sumberarum III. The subjects of this study were teachers and students IV of SD Negeri Sumberarum III who collected 11 students. Data collection techniques using the method of observation, documentation and field notes. The procedure in this study has four stages, namely planning, implementation, observation and reflection. This study consisted of two cycles with the application of the STAD method. Performance indicators in this study are expected to student learning activities in the learning process can reach a minimum of 75% of the total 11 students. Data analysis techniques used comparative descriptive techniques and critical analysis techniques. The results showed that the application of the STAD method had been able to increase science learning activities in fourth grade students, as evidenced in the second cycle as many as 36.4% of active students and 50.0% of very active students. The teacher's activity in applying the STAD method increased in each cycle, in the first cycle the teacher's activity reached 66.67%, in the second cycle the teacher's activity increased to 91.67%. Based on the data from the classroom action research, it can guarantee that the implementation of the STAD strategy can increase the activeness of learning science in grade IV students at SDN Sumberarum III.